2023
DOI: 10.1002/cncr.34607
|View full text |Cite
|
Sign up to set email alerts
|

Spatial PD‐L1, immune‐cell microenvironment, and genomic copy‐number alteration patterns and drivers of invasive‐disease transition in prospective oral precancer cohort

Abstract: Background Studies of the immune landscape led to breakthrough trials of programmed death‐1 (PD‐1) inhibitors for recurrent/metastatic head and neck squamous cell carcinoma therapy. This study investigated the timing, influence of somatic copy‐number alterations (SCNAs), and clinical implications of PD‐L1 and immune‐cell patterns in oral precancer (OPC). Methods The authors evaluated spatial CD3, CD3/8, and CD68 density (cells/mm2) and PD‐L1 (membranous expression in cytokeratin‐positive intraepithelial neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…23,24,40,41 This may be due to deletions encompassing the type I interferon gene cluster, 42 which is often co-deleted with the tumor suppressor CDKN2A, highlighting a key mechanism of immune evasion. 43 In our immunogenomic studies, only pretreat- 44 and associated with an immune-cold signal in OSCC 23 that is enhanced by larger deletions extending to the telomeric band at 9p24.1. 40 We speculate that resistance to the PD-1 inhibitor in this aggressive oral precancerous disease trial may have arisen during ICT…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…23,24,40,41 This may be due to deletions encompassing the type I interferon gene cluster, 42 which is often co-deleted with the tumor suppressor CDKN2A, highlighting a key mechanism of immune evasion. 43 In our immunogenomic studies, only pretreat- 44 and associated with an immune-cold signal in OSCC 23 that is enhanced by larger deletions extending to the telomeric band at 9p24.1. 40 We speculate that resistance to the PD-1 inhibitor in this aggressive oral precancerous disease trial may have arisen during ICT…”
Section: Discussionmentioning
confidence: 78%
“…In our immunogenomic studies, only pretreatment 9p21.3 deletion yielded statistically significant differences: 6 of 10 patients with 9p21.3 deletion in baseline biopsies later developed cancer. We have previously shown that 9p21.3 copy-number loss is generally a focal event in oral precancer and associated with an immune-cold signal in OSCC that is enhanced by larger deletions extending to the telomeric band at 9p24.1 . We speculate that resistance to the PD-1 inhibitor in this aggressive oral precancerous disease trial may have arisen during ICT resulting from increasing 9p deletion size to encompass 9p24.1, leading to low expression of the therapeutic target (PD-L1) and other immune gene depletion .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…'Lymphocytic immune response' is more compatible with descriptions of the immune microenvironment in OED, in which high CD3/8+ lymphocyte density may predict better squamous cell carcinoma (SCC)-free survival, particularly in OED that does not express PD-L1. 26 LIR could represent the intra-epithelial/dysplastic counterpart to tumour infiltrating lymphocytes (TIL) well recognised in many cancers, including head and neck SCC, where a minority of patients benefit from PD-1/ PD-L1 blockade. [27][28][29][30][31] Not unsurprisingly, in this cohort one OED with LIR had a focus of invasive SCC with TILs (Figure 9F).…”
Section: Discussionmentioning
confidence: 99%